2020
DOI: 10.1080/09712119.2020.1751642
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of steroidal implants to improve beef cattle growth: a review

Abstract: For more than 60 y, beef cattle producers have safely used various types of growth-enhancing technology (GET) such as steroidal implants with anabolic activity and orally active beta-adrenergic agonists to increase skeletal muscle growth rate, improve carcass leanness, increase average daily gain (ADG), and alter dry matter intake (DMI) compared to non-treated cattle. Generally, the use of a GET increases ADG and only moderately affects DMI relative to non-treated cattle; subsequently, this enhances the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 60 publications
1
45
0
Order By: Relevance
“…In recent years, the use of coated implants has become an alternative for producers who do not want to reimplant cattle during the time cattle are on feed. Coated implants come in a variety of doses, polymer coating types, and ratios of androgen to estrogen ( Smith and Johnson, 2020 ). Reimplanting must be done properly to avoid undue stress on cattle ( Stanton, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the use of coated implants has become an alternative for producers who do not want to reimplant cattle during the time cattle are on feed. Coated implants come in a variety of doses, polymer coating types, and ratios of androgen to estrogen ( Smith and Johnson, 2020 ). Reimplanting must be done properly to avoid undue stress on cattle ( Stanton, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current results are similar to others ( Guiroy et al, 2002 ; Hilscher et al, 2016 ; Ohnoutka et al, 2018 ) that also have documented that greater total doses of anabolic steroid hormones in steers ( Hilscher et al, 2016 ) and heifers ( Ohnoutka et al, 2018 ) do not alter final BW, ADG, or G:F. Additionally, it has been previously demonstrated that steers administered a coated implant (initial and delayed-release implant formulation), Revalor-XS (Merck Animal Health, 200 mg TBA and 40 mg E 2 ) 213 d prior to harvest had greater final BW, ADG, and improved G:F compared to steers administered a single Revalor-200 (Merck Animal Health, 200 mg TBA and 20 mg E 2 ) at either 213 or 143 d prior to harvest ( Smith et al, 2018 ), indicating the benefits in performance when cattle are exposed to hormone payout over the entirety of the feeding period. Reasons for greater total doses of steroid hormones in heifers not resulting in improved performance responses could be attributed to greater levels of endogenous E 2 in circulation compared to steers ( Heitzman, 1976 ) or the fact that absolute growth response in heifers is lesser than steers due to a smaller response surface ( Smith and Johnson, 2020 ). This reduced the effect of the added hormone in heifers also could be an effect of heifers having a lower muscle-to-fat ratio and a lower basal growth rate than steers and, therefore, an effect of any growth-promoting technology will be less in heifers than steers ( Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary goals of the feedlot industry is to increase animal growth performance and gain efficiency during all stages of the feedlot production phase. Production enhancement technologies (e.g., steroidal implants with anabolic activity and beta-adrenergic agonist) are routinely employed in North American feedlots to increase production efficiencies ( Johnson et al, 2013 ; Smith and Johnson, 2020 ). Additionally, feed grade and injectable antimicrobials are used in North American beef production to prevent and treat illness in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The androgenic constituent of steroidal implants, TBA, has a direct effect on skeletal muscle that increases muscle tissue anabolism while decreasing muscle tissue catabolism, thus increasing net protein synthesis ( Smith and Johnson, 2020 ). Previous research has shown that the anabolic effect of steroidal implants results in decreased serum concentration of urea-N (SUN) concentrations after implantation with a combination TBA + E 2 implant ( Smith et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%